Estratégias de polidez no período pandêmico: interações comunicativas em redes sociais - Braga, Marilene Aparecida Paula da Costa (2024)
This dissertation is part of the line of research “Text and discourse in oral and written modalities”, of the Postgraduate Program in Portuguese Language at the Pontifical Catholic University of São Paulo, and its theme is the study of politeness strategies in social networks, during the pandemic period. We seek to answer the following questions: i) What politeness strategies are present in communications carried out on the social networks Facebook and Instagram during the pandemic period? ii) What verbal and non-verbal elements constitute politeness strategies in these interactions? Our general objective is to contribute to the understanding of politeness strategies in virtual interactions, and as specific objectives, to identify, describe, analyze and interpret the politeness strategies present in the selected corpus, as well as discuss users' choices regarding the elements verbal and non-verbal politeness. In order to achieve them, we based ourselves theoretically: a) with regard to the approach to politeness, in the studies of Goffman (2002 [1975]; 2011 [1967]), Brown and Levinson (1987), Kerbrat-Orecchioni ( 2006; 2017), Fávero (2008), Seara e Cabral (2017), Marcuschi (2003), Briz (2005; 2013) and Carreira (2014); b) with regard to social networks and interactions, in studies of Recuero (2009), Aguiar (2007), Goffman (2011 [1967]), Kerbrat-Orecchioni (2006), Santaella (2006), Martino (2014) , Carmelino and Kogawa (2020) and Damasceno (2020). The corpus consists of 12 posts and their respective comments, totaling 124, collected from March 2020 to March 2021. The results point to the recurrent use of positive politeness mitigation strategies consisting of verbal elements that present the use of depersonalization and apology, and by non-verbal elements consisting of emojis of hands together and applause